Efektivitas Wedge Exercise Prone Position Terhadap Kemampuan Mengangkat Kepala Bayi Usia 0-12 Minggu - Anitriadna, Shinta, Agus Widodo, S.Fis., M.Fis (2016)
Lifting head is the benchmark of the first motoric achieved. Good head control can be the basis of the development for the refinement of the other benchmarks. The exercise program of wedge become one of the interventions applied to stimulate the ability of baby lifting head at the age of 0-12 weeks. To determine the effectiveness of wedge exercise with a 25 ̊ slope facedown on the ability of lifting head of baby at the age of 0-12 weeks. This type of research is descriptive and analytical research with pre and post control design by using treatment group and control group. There are 2 respondents in the treatment group, given wedge exercise performed for 5 minutes with a frequency of exercise two times a week for 12 weeks and 2 respondents in the control group, untreated. The ability of lifting head was assessed by using GMFM-88 form scale. Based on the wedge exercise given for the treatment groups, 2 respondents obtained post test value 53% and 30%. Meanwhile, at the control group, 2 respondents obtained post test values 25% and 21%. There is an effect of wedge exercise on the ability of lifting head of baby at the age 0-12 weeks. Keywords: wedge exercise, the ability of lifting head, 0-12 weeks old baby.